2018
DOI: 10.1186/s12885-017-3857-5
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab without chemotherapy in the adjuvant treatment of breast cancer: subgroup results from a large observational study

Abstract: Background: The topic of trastuzumab therapy without chemotherapy in early breast cancer (EBC) has been repeatedly discussed at international consensus meetings, but is compromised by the lack of solid evidence from clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Dual HER2 blockade therapies without chemotherapy have demonstrated efficacy in the preoperative setting in patients with HER2-positive breast cancer 24 . However, data about non-chemotherapy HER2 blockade including single agent trastuzumab is limited in the adjuvant setting 25 . Future trials are warranted to explore this option in smaller HER positive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Dual HER2 blockade therapies without chemotherapy have demonstrated efficacy in the preoperative setting in patients with HER2-positive breast cancer 24 . However, data about non-chemotherapy HER2 blockade including single agent trastuzumab is limited in the adjuvant setting 25 . Future trials are warranted to explore this option in smaller HER positive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…During these 6–8 cycles, there are potential cost savings with respect to healthcare professional time and consumables with IV trastuzumab administration by piggy backing on the costs that must be applied for IV chemotherapy administration during concurrent or sequential administration. The combination of trastuzumab with chemotherapy is usual practice (94%) during adjuvant therapy across German hospitals [ 21 ], whereas trastuzumab monotherapy is the norm in the Southeast Netherlands (100%) [ 22 ] and most common in Southeast Wales (83%) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from a large observational study suggested that trastuzumab-plus-chemotherapy should remain the preferred option for all patients indicated for adjuvant treatment, and that a low proportion of patients need an alternative treatment approach, either because of contraindications or the patient's preference. Trastuzumab monotherapy might be a reasonable option [10], but to our knowledge, no prospective data exist to suggest that prospective adjuvant trastuzumab alone can offer a bene t over no adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%